2022
DOI: 10.3389/fgene.2022.917007
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Necroptosis-Related Gene Signature in Skin Cutaneous Melanoma Prognosis and Tumor Microenvironment

Abstract: Background: Necroptosis has been identified recently as a newly recognized programmed cell death that has an impact on tumor progression and prognosis, although the necroptosis-related gene (NRGs) potential prognostic value in skin cutaneous melanoma (SKCM) has not been identified. The aim of this study was to construct a prognostic model of SKCM through NRGs in order to help SKCM patients obtain precise clinical treatment strategies.Methods: RNA sequencing data collected from The Cancer Genome Atlas (TCGA) we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 52 publications
0
15
0
Order By: Relevance
“…However, only a limited number of HCC patients benefited from it, the efficacy of immunotherapy is affected by many factors specific to the individual, such as the unique TIME, the expression of the immune checkpoint genes and the related gene mutation levels. Tumor immune microenvironment (TME) has a significant impact on tumor progression process and therapy response, so that many researchers would conduct immune cell infiltration and TME analysis of tumors of their interest ( 49 51 ). In our work, with the application of CIBERSORT algorithm and ssGSEA approach, we found that macrophage M0 infiltration was greater in the high-risk group, while T cells CD4 memory resting was less infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…However, only a limited number of HCC patients benefited from it, the efficacy of immunotherapy is affected by many factors specific to the individual, such as the unique TIME, the expression of the immune checkpoint genes and the related gene mutation levels. Tumor immune microenvironment (TME) has a significant impact on tumor progression process and therapy response, so that many researchers would conduct immune cell infiltration and TME analysis of tumors of their interest ( 49 51 ). In our work, with the application of CIBERSORT algorithm and ssGSEA approach, we found that macrophage M0 infiltration was greater in the high-risk group, while T cells CD4 memory resting was less infiltration.…”
Section: Discussionmentioning
confidence: 99%
“…CM is a lethal malignancy with an alarming and increasing incidence rate worldwide over the past years ( Song et al, 2022 ). It is well known that metastasis is a main factor leading to poor efficacy and prognosis of CM patients, despite the introduction of novel therapeutic approaches such as immunotherapy ( Burzi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Finally, according to the drug sensitivity analysis, we screened 19 drugs with different sensitivities in the two risk groups, which may provide guidance for the treatment of melanoma. Song et al (2022a) , Song et al (2022b) utilized coagulation and apoptosis related genes to better predict the prognosis and tumor microenvironment of cutaneous melanoma. Although the recent researches on the model of cuproptosis predicting the prognosis of melanoma has shown a good prediction effect, it has not been verified in vivo or in vitro , and the true prediction effect of the model is still uncertain ( Liu et al, 2022 ; Zhou et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%